A study into the effect of sugar cane fires on AC corona noise : development of a laboratory simulation and measurement process - Vosloo, Wallace L.(Wallace Lockwood) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Ing.) -- University of Stellenbosch, 1992.